Genomic predictors of trainability - Bouchard, C. (Experimental Physiology, 2012)
The concept of individual differences in the response to exercise training or trainability was defined three decades ago. In a series of experimental studies with pairs of monozygotic twins, evidence was found in support of a strong genotype dependency of the ability to respond to regular exercise. In the HERITAGE Family Study, it was observed that the heritability of the maximal oxygen uptake response to 20 weeks of standardized exercise training reached 47% after adjustment for age, sex, baseline maximal oxygen uptake and baseline body mass and composition. Candidate gene studies have not yielded as many validated gene targets and variants as originally anticipated. Genome-wide explorations have generated more convincing predictors of maximal oxygen uptake trainability. A genomic predictor score based on the number of favourable alleles carried at 21 single nucleotide polymorphisms appears to be able to identify low and high training response classes that differ by at least threefold. Combining transcriptomic and genomic technologies has also yielded highly promising results concerning the ability to predict trainability among sedentary people.